2021
DOI: 10.51791/njap.v34i1.2433
|View full text |Cite
|
Sign up to set email alerts
|

THE FEEDING VALUE OF CASSAVA MEAL DIETS FOR GROWING JAPANESE QUAIL (Coturnix Coturnix Japonica)

Abstract: A six-week feeding trial was conducted to determine the replacement value of Cassava meal for maize in a piratical quail diet. It involved ninety six day-old quail chicks housed in cages in a brooding house. Four isonitrogenous (22%mde protein) diets incorporating graded levels (0.0, 15, 25 and 35%) of cassava meal as a replacement for maize were tested. The diets were also isocaloric (280Kcal/kg  M. E.) and contained crude protein (25.53%; diet 1, 25.00%; diet 2, 24.34%; diet 3and 24.00% diet4) and were repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…You saved more money /kg meat gained when SFM or RSM was incorporated into diets since feed costs /kg meat gained were lowered. Consequently, you fed less and gained more weight, similar results have been reported when using other non-conventional feed sources [76,77].…”
Section: Discussionsupporting
confidence: 76%
“…You saved more money /kg meat gained when SFM or RSM was incorporated into diets since feed costs /kg meat gained were lowered. Consequently, you fed less and gained more weight, similar results have been reported when using other non-conventional feed sources [76,77].…”
Section: Discussionsupporting
confidence: 76%
“…Broiler chickens fed ration comprising cassava pellets had improved feed consumption compared to birds fed rations with cassava chips or maize [16]. The reports of Edache et al, [24] indicated that 35% cassava meal based ration is suggested for growing Japanase quail. Cockerel starter birds could tolerate only about 28% level of cassava sievate in their ration [52].…”
Section: Use Of Cassava (Manihot Esculenta Crantz) Meal In Poultry Dietmentioning
confidence: 98%
“…Compared to chicken-fed rations with cassava chips or maize, broiler chicken-fed rations containing cassava pellets exhibited improved feed consumption [26]. For growing Japanese quail, about 35% cassava meal-based ration is suggested [27]. Cockerel starter birds can tolerate only about 28% level of cassava sievate in their ration [28].…”
Section: Cassava (Manihot Esculenta) In Chicken Dietmentioning
confidence: 99%